Strategi Optimalisasi Perdagangan Ekspor Kopi Di Indonesia Melalui Situs Trademap - Hakim Mahdi Zakariya; Lia Nirawati (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
Export trade of coffee in Indonesia plays a crucial role in the country's economy; however, challenges and dynamics in the global market demand the development of an optimal strategy to enhance the competitiveness of Indonesian coffee products. This research aims to formulate an optimization strategy for coffee export trade by leveraging information provided by the Trademap website. The research method involves analyzing Indonesian coffee export data from the Trademap site, identifying global market trends, and evaluating relevant trade policies and regulations. The results of this analysis will form the basis for designing a strategy to increase market share and the export value of Indonesian coffee. The proposed strategy includes strengthening product branding, diversifying target export markets, improving the quality and innovation of products, and optimizing the supply chain to enhance logistic efficiency. Additionally, the integration of information technology and communication in trade management is incorporated to expedite information access and minimize business risks. The implementation of this strategy is expected to make a positive contribution to the growth of Indonesia's coffee exports, opening opportunities for access to new markets, and increasing the value-added of products. By tapping into the information potential of the Trademap site and developing adaptive strategies, Indonesia can effectively navigate the dynamics of the global market, strengthen its position as a leading coffee producer, and enhance the well-being of business actors in the coffee sector.